Hydrilla tuber weevil Bagous affinis Hustache (Insecta: Coleoptera: Curculionidae) - Emma Weeks (EDIS)
Bagous affinis Hustache is a semi-aquatic weevil that feeds on the aquatic invasive plant Hydrilla verticillata (L.f.) Royle. The larvae of the weevil mine hydrilla tubers, and the adults feed on the submerged stems and leaves. The weevil was discovered during surveys for biological control agents for hydrilla in Pakistan in 1980 and was first introduced to the U.S. in Florida from India in 1987. This 5-page fact sheet was written by Emma Weeks, and published by the UF Department of Entomology and Nematology, June 2014.